2002
DOI: 10.1007/s00425-002-0786-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of amino acid uptake in conifers by exogenous and endogenous nitrogen

Abstract: Although an accumulating amount of research clearly indicates that plants are capable of taking up exogenous amino acids, the actual importance of such organic N sources for plant N nutrition is under debate. In this study, we show that amino acid uptake by Scots pine (Pinus sylvestris L.) is significantly decreased by elevated internal NH(4)(+) levels, while it increases following exposure to exogenous amino acids. Furthermore, amino acid uptake is larger in N-deficient plants than in plants grown with a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 32 publications
7
35
2
1
Order By: Relevance
“…Amino acids may constitute a significant part of the N absorbed by plants in terrestrial ecosystems, especially under low N conditions (Harrison et al, 2000;Nasholm et al, 1998Nasholm et al, , 2000Nasholm et al, , 2009Persson and Nasholm, 2002). Several amino acid transporters have been described in plants, conferring ability to absorb amino acids from the soil solution (Lipson and Nasholm, 2001).…”
Section: E Gioseffi Et Al: Organic and Inorganic N Interactions In mentioning
confidence: 99%
See 2 more Smart Citations
“…Amino acids may constitute a significant part of the N absorbed by plants in terrestrial ecosystems, especially under low N conditions (Harrison et al, 2000;Nasholm et al, 1998Nasholm et al, , 2000Nasholm et al, , 2009Persson and Nasholm, 2002). Several amino acid transporters have been described in plants, conferring ability to absorb amino acids from the soil solution (Lipson and Nasholm, 2001).…”
Section: E Gioseffi Et Al: Organic and Inorganic N Interactions In mentioning
confidence: 99%
“…They each have different specificity and affinity for amino acids (Hirner et al, 2006;Lee et al, 2007;Svennerstam et al, 2008). Amino acid transporters are less well characterised in other species but it is well documented that amino acid uptake occurs in a wide range of species including gymnosperms (Nasholm et al, 1998;Persson and Nasholm, 2002), dicots (Ge et al, 2009;Kielland, 1994;Nasholm et al, 1998Nasholm et al, , 2000Streeter et al, 2000) and monocots (Biernath et al, 2008;El-Naggar et al, 2009;Henry and Jefferies, 2003;Jamtgard et al, 2008Jamtgard et al, , 2010Kielland, 1994;Lipson et al, 1999;Nasholm et al, 1998Nasholm et al, , 2000Nasholm and Persson, 2001;Schimel and Chapin, 1996;Streeter et al, 2000;Thornton, 2001;Thornton and Robinson, 2005;Yamagata and Ae, 1999). However, the importance and significance of organic N as a source of crop N under different management systems is still not well established.…”
Section: E Gioseffi Et Al: Organic and Inorganic N Interactions In mentioning
confidence: 99%
See 1 more Smart Citation
“…더욱이 아미노산 트랜스포터가 몇 가지의 식물 종 에서 동정되었고, 아미노산 흡수의 메커니즘에 대한 연구 도 진행되고 있다 (Frommer et al, 1993;Montamat et al, 1999;Neelam et al, 1999;Persson and Nasholm, 2002;Persson and Nasholm, 2003;Zhou et al, 1999). 특히, …”
Section: 한편 많은 식물 종에서 시용한 아미노산을 비교적 높은unclassified
“…Experiments of amino acid uptake from incubation solutions [26,27] and soils [28,27], using many plant species representing a wide variety of plant types, have shown that rates of organic N uptake can be high compared with that of inorganic N in these ecosystems. This conclusion took into account free amino acid concentration in soils and root uptake kinetics [6,19,14].…”
Section: Bromeliads and Orchidsmentioning
confidence: 99%